Digital Microfluidic Platform for Multiplexing Enzyme Assays: Implications for Lysosomal Storage Disease Screening in Newborns - Sista, Ramakrishna S; Eckhardt, Allen E; Wang, Tong; Graham, Carrie; Rouse, Jeremy L; Norton, Scott M; Srinivasan, Vijay; Pollack, Michael G; Tolun, Adviye A; Bali, Deeksha; Millington, David S; Pamula, Vamsee K (Clinical chemistry (Baltimore, Md.), 2011)
Newborn screening for lysosomal storage diseases (LSDs) has been gaining considerable interest owing to the availability of enzyme replacement therapies. We present a digital microfluidic platform to perform rapid, multiplexed enzymatic analysis of acid α-glucosidase (GAA) and acid α-galactosidase to screen for Pompe and Fabry disorders. The results were compared with those obtained using standard fluorometric methods. We performed bench-based, fluorometric enzymatic analysis on 60 deidentified newborn dried blood spots (DBSs), plus 10 Pompe-affected and 11 Fabry-affected samples, at Duke Biochemical Genetics Laboratory using a 3-mm punch for each assay and an incubation time of 20 h. We used a digital microfluidic platform to automate fluorometric enzymatic assays at Advanced Liquid Logic Inc. using extract from a single punch for both assays, with an incubation time of 6 h. Assays were also performed with an incubation time of 1 h. Assay results were generally comparable, although mean enzymatic activity for GAA using microfluidics was approximately 3 times higher than that obtained using bench-based methods, which could be attributed to higher substrate concentration. Clear separation was observed between the normal and affected samples at both 6- and 1-h incubation times using digital microfluidics. A digital microfluidic platform compared favorably with a clinical reference laboratory to perform enzymatic analysis in DBSs for Pompe and Fabry disorders. This platform presents a new technology for a newborn screening laboratory to screen LSDs by fully automating all the liquid-handling operations in an inexpensive system, providing rapid results.